Pengalaman Belajar Matematika di Masa Pandemi Covid 19 dan Implikasinya Terhadap Self Efficacy Peserta Didik - Shinta Kusuma Dewi (Universitas Cokroaminoto Palopo, 2023)
The pandemic has not only affected the economic system but has greatly affected the education sector in Indonesia, one of which is in schools. The learning system continues to run using technology-based distance learning methods. So that this method greatly affects the learning for a year of students, one of which is learning mathematics. This study aims to determine the influence and relationship between a year's learning in mathematics and student self-efficacy. Researchers in this study used a survey method with a quantitative approach. The subjects in this study were students of SMP who were taken from six classes in grade 9, totaling 200 respondents. The collected data will be tested with a correlation test using SPSS. The results of the study based on the results of the Pearson correlation test stated that the correlation value was 0.636 which means there is a strong correlation. That is, teaching throughout the year learning mathematics affects and there is a relationship with student self-efficacy.